2020
DOI: 10.1016/j.drugalcdep.2020.108207
|View full text |Cite
|
Sign up to set email alerts
|

Impact of medications for opioid use disorder among persons hospitalized for drug use-associated skin and soft tissue infections

Abstract: Background: Skin and soft tissue infections (SSTI) are common complications of injection drug use. We aimed to determine if rehospitalization and recurrent SSTI differ among persons with opioid use disorder (OUD) hospitalized for SSTI who are initiated on MOUD within 30 days of discharge and those who are not. Methods:We performed a retrospective analysis of commercially insured adults aged 18 years and older in the U.S. with OUD and hospitalization for injection-related SSTI from 2010-2017. The primary exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Compared to other cohorts of patients with SIRI, the 100% rate of post-discharge MOUD is especially notable. National US cohorts have demonstrated <10% receipt of MOUD following SIRI hospitalization [ 37 , 38 ] and even in select locales with higher addiction treatment access, only 25–50% of patients with SIRI receive post-hospital MOUD [ 10 , 39 ]. We believe that the control of cravings and withdrawal facilitated high rates of antibiotic completion in a group of individuals who had previously struggled immensely with adherence to medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other cohorts of patients with SIRI, the 100% rate of post-discharge MOUD is especially notable. National US cohorts have demonstrated <10% receipt of MOUD following SIRI hospitalization [ 37 , 38 ] and even in select locales with higher addiction treatment access, only 25–50% of patients with SIRI receive post-hospital MOUD [ 10 , 39 ]. We believe that the control of cravings and withdrawal facilitated high rates of antibiotic completion in a group of individuals who had previously struggled immensely with adherence to medical care.…”
Section: Discussionmentioning
confidence: 99%
“…We included OATS study participants who survived at least one emergency (unplanned) hospitalization with skin and soft-tissue infection, sepsis or bacteremia, endocarditis, osteomyelitis, septic arthritis, or central nervous system infections (brain or spine abscess), identified using ICD-10 codes (see Fig 1 for study inclusion flow diagram; see S1 Table for ICD codes). We began with codes used in prior studies [ 8 , 29 , 39 41 ] and adapted our final list based on literature review and clinical input from the investigator team.…”
Section: Methodsmentioning
confidence: 99%
“…Prior analyses of potential benefits of OAT after hospitalization with injecting-related infections have been limited by small sample sizes with wide confidence intervals (CIs) [ 38 , 39 ]. Three administrative linkage cohort studies (all from US insurance claims data) have assessed associations between use of OAT and outcomes after hospitalization with injecting-related bacterial or fungal infections [ 39 41 ]. One study identified a reduced risk of death after hospitalizations with injecting-related endocarditis, but did not assess rehospitalizations [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations